Role of molecular tools in modern zoology (Zoological Records and Reviews, 2025)
Molecular tools have transformed zoology from a discipline dependent on morphological observation and field survey toone capable of resolving population structure, species boundaries, dietary ecology, pathogen dynamics, and landscapeconnectivity from minute biological samples or environmental residues. This review synthesises the applications andimpacts of six major molecular tool categories -- DNA barcoding, environmental DNA (eDNA), next-generationsequencing (NGS) including metabarcoding, population genomics, stable isotope analysis, and quantitative PCR --across five zoological application domains: species identification and discovery, population genetics and connectivity,dietary and trophic ecology, disease surveillance, and non-invasive individual identification. Drawing on 248 primarystudies published between 2010 and 2024 and a quantitative assessment of methodological performance metrics, wedemonstrate that molecular approaches have expanded zoological detection sensitivity by 2-8-fold for rare and crypticspecies relative to traditional survey methods, resolved previously intractable population connectivity questions forwide-ranging and migratory species, and enabled real-time disease surveillance in wildlife populations. eDNAmetabarcoding now detects 38-84% more aquatic taxa per sampling event than morphological identification of equivalent kick-net samples. Population genomics (SNP arrays, whole-genome resequencing) has replaced microsatellite-based population genetics as the standard for conservation genetics in the past five years, providing 100-10,000-fold greater marker resolution with decreasing costs. Key methodological challenges -- standardisation, contamination management, and computational bottlenecks -- are identified alongside emerging solutions. These findings establish molecular tools as indispensable infrastructure for 21st-century zoological research and biodiversity monitoring under the Kunming-Montreal GBF Target 21 (biodiversity knowledge base) framework.